Separatatus Chen & Wu (Hymenoptera: Braconidae: Alysiinae) newly recorded from Thailand, with description of one new species and one new combination - Yao, Junli; van Achterberg, Cornelis; Sharkey, Michael J.; Chen, Jiahua (Zootaxa, 2018)
Separatatus Chen & Wu, 1994, is reported for the first time from Thailand and one new species is described and illustrated: Separatatus xuexincheni n. sp. In addition, one species is newly recorded from Thailand (S. parallelus Zhu et al., 2017) and we transfer one species from Phasmidiasta to Separatatus: S. malaysiae (Fischer, 2006) n. comb. A key to species of the genus Separatatus is presented.